The Relationship Between Hyperglycemia and the Rheumatoid Factor in the Serum of Diabetic Patients - Baghdad Science Journal (مجلة بغداد للعلوم)
This study was conducted to determine the relationship between two most common diseases in Iraqis patients , which are Diabetic mellitus (DM) and Rheumatoid Arthritis (RA); seeking rheumatoid factor in hyperglycemic sera. The results revealed that ; 62.5% of hyperglycemic (HG) patients had positive rheumatoid factor (RF) . No difference in number between both gender of HG patients (20 males and 20 females ) , RF reaction was nearly similar in males and females of HG patients ( 12 &13 respectively ) . Only 40% out of patient controls had positive RF . None of the apparently healthy subjects had positive RF .